Individui, comunità e istituzioni in emergenza Intervento psico-socio-pedagogico e lavoro di rete nelle situazioni di catastrofe - Mariantoni , Stefania (I territori dell'educazione - Open Access, 2018)
Starting from the experiences of the "Velino for Children" project, which has worked in the Lazio territories hit by the earthquakes of 2016-2017, this book focuses on the models of psycho-socio-pedagogical intervention (at school, in the family, in institutions that support communities, etc.) that can work for the promotion of individual and community resilience. For this reason, the work is aimed at all those actors (administrators, managers, service coordinators, teachers, educators, social workers, psychologists) who, within the emergencies, are committed to favoring the processes of recovery and of social and educational reconstruction.